1999
DOI: 10.1093/intimm/11.7.1065
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-induced arthritis development requires αβ T cells but not γδ T cells: studies with T cell-deficient (TCR mutant) mice

Abstract: Collagen type II (CII)-induced arthritis (CIA) in mice is a model for rheumatoid arthritis (RA) in which the role of T lymphocytes remains controversial. To clarify this, we have bred a targeted gene deletion of TCR beta or delta loci into two mouse strains susceptible to CIA, the B10.Q and DBA/1 strains. The TCRbeta-/- mice lacked alphabeta T cells, which was compensated by an expansion of B cells, gammadelta T cells and NK cells. The beta-/- mice, but not control beta+/- littermates, were completely resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
65
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 50 publications
4
65
2
Order By: Relevance
“…A direct comparison of the absolute numbers of IL-17-producing ␥/␦ T cells with the absolute numbers of Th17 cells simultaneously in each joint of mice with CIA was performed for the first time. Although it is known that ␥/␦ T cells are not necessary for the induction of CIA, because ␥/␦ TCR-deficient mice can mount CIA (37), the present findings in the kinetics study and adoptive transfer experiments, together with previous reports (16,18,38), suggest that not only Th17 cells but also IL-17-producing ␥/␦ T cells contribute to the exacerbation of CIA. In contrast, ␣/␤ ⌻ cells, especially Th17 cells, are essential for the induction of CIA, because ␣/␤ TCR-deficient mice cannot mount CIA (37).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…A direct comparison of the absolute numbers of IL-17-producing ␥/␦ T cells with the absolute numbers of Th17 cells simultaneously in each joint of mice with CIA was performed for the first time. Although it is known that ␥/␦ T cells are not necessary for the induction of CIA, because ␥/␦ TCR-deficient mice can mount CIA (37), the present findings in the kinetics study and adoptive transfer experiments, together with previous reports (16,18,38), suggest that not only Th17 cells but also IL-17-producing ␥/␦ T cells contribute to the exacerbation of CIA. In contrast, ␣/␤ ⌻ cells, especially Th17 cells, are essential for the induction of CIA, because ␣/␤ TCR-deficient mice cannot mount CIA (37).…”
Section: Discussioncontrasting
confidence: 47%
“…Although it is known that ␥/␦ T cells are not necessary for the induction of CIA, because ␥/␦ TCR-deficient mice can mount CIA (37), the present findings in the kinetics study and adoptive transfer experiments, together with previous reports (16,18,38), suggest that not only Th17 cells but also IL-17-producing ␥/␦ T cells contribute to the exacerbation of CIA. In contrast, ␣/␤ ⌻ cells, especially Th17 cells, are essential for the induction of CIA, because ␣/␤ TCR-deficient mice cannot mount CIA (37). In addition, IL-17-producing invariant NK T cells in CIA have been reported recently (37), but these cells were not analyzed in the current study.…”
Section: Discussioncontrasting
confidence: 47%
“…Earlier studies showed that the autoimmune diseases experimental auto-immune encephalomyelitis (EAE) and collagen-induces arthritis (CIA) can be induced more easily in CD200 −/− mice than in wild type mice . Although this phenomenon has previously been attributed to myeloid cells, lymphocytes also are involved in the development of these auto-immune diseases (Corthay et al, 1999;Sospedra and Martin, 2005). The current finding that CD200R is clearly expressed on some lymphocyte subsets, and upregulated after stimulation, might indicate that lack of CD200R signalling in lymphocytes is also involved in development of auto-immunity in CD200 −/− mice.…”
Section: Discussionmentioning
confidence: 65%
“…These lymphocytes further induce an autoimmune response against CII that leads to the development of arthritis. It has been shown that CIA is critically dependent on B cells as well as the complement system, whereas T cells do not seem to play an essential role (12,13,31). CIA is a permanent and relapsing disease involving inflammation, tissue destruction, and tissue repair of the affected joints.…”
Section: Discussionmentioning
confidence: 99%
“…CIA is induced by intradermal immunizations with the major cartilage protein component type II collagen (CII) (8,11). CIA is dependent both on B and T cells as well as the complement system (12,13).…”
mentioning
confidence: 99%